ANALISIS PENGARUH NON PERFORMING FINANCING DAN FINANCING TO DEPOSIT RATIO TERHADAP VOLUME PEMBIAYAAN PADA PERBANKAN SYARIAH DI INDONESIA DENGAN DANA PIHAK KETIGA SEBAGAI VARIABEL - Whidaningayu, Endriana (Program Studi Akuntansi, Universitas Kuningan, 2015)
This study aims to analyze the effect of the NPF ( non performing financing) and FDR (financing to deposit ratio) to the volume of financing of Islamic Banks in Indonesia with third-party funds as a mediating variable. The population in this study are all Islamic banks in Indonesia who registered at Bank Indonesia.Ã‚Â Determination of the sample used by using purposive sampling, then obtain three Islamic banks were analyzed by mediation regression analysis which use multiple causal step method.Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â The results of this study indicate that the NPF has positive significant to the volume of financing of Islamic banks in Indonesia, FDR has no significant to the volume of financing of Islamic banks in Indonesia, NPF has positive significant to the third-party funds, FDR has no significant to the third-party funds, the third-party funds has positive significant to the volume of financing of Islamic banks in Indonesia, the third-party funds has significant effect in mediating NPF to the volume of financing of Islamic banks in Indonesia.